Pengaruh Kualitas Pelayanan dan Biaya Operasional terhadap Kepuasan Pelanggan pada Stasiun Kereta Api Medan - Tahfizah, Dina; Nasution, Anio Indah Lestari; Aslami, Nuri (Masyarakat Ekonomi Syariah Bogor, 2024)
This research aims to find out and analyze how and how much influence Service Quality, Number of Passengers and Operational Costs have on Customer Satisfaction at the Medan Train Station, North Sumatra. The research method used in this research is a quantitative descriptive approach. The type of data used is primary data obtained from respondents and companies. The subjects in the research were PT Kereta Api Indonesia Medan, North Sumatra and the objects of this research were 100 respondents. The test tool used in this research is SPSS 20.0 to test classical assumptions, multiple regression analysis, and hypothesis testing. Based on the results of the hypothesis test, namely the t test, it shows that service quality has a positive and significant effect on customer satisfaction. Operational Costs with test results that the number of passengers has a positive and significant effect on customer satisfaction. And the results of the F test show that Service Quality, Number of Passengers and Operational Costs simultaneously have a significant effect on customer satisfaction with an F Prob value of 0.0000. The results of this test show that the service quality and operational cost variables contribute 66.6% to the Customer Satisfaction variable.